Effect of Crayfish Waste Meal on Performance Characteristics and Nutrient Retention of Broiler Finishers - Asafa, A.R.; Ologhobo, A.D.; Adejumo , I.O. (International Journal of Poultry Science, 2012)
The study investigated the effect of crayfish waste meal on the performance characteristics and nutrient retention in broiler finisher. 150 one day old chicks were used for the study which lasted for 9 weeks. The result of the study showed that the average dry matter intake ranged from 1918.96 g in broiler chicken fed diet IV (25%FM:75%CWM) to 2141.60g in diet V (100% CWM) chickens. There was no significant differences (p>0.05) between treatment means. Birds fed the control diet (100%FM) recorded the highest gain (787.30 g) followed by those fed diet III (50%FM; 50%CWM) while the least gain (679.00 g) was by diet V (100%CWM) chickens. No significant (p>0.05) difference was observed between the treatment means. The feed conversion ratio was best (2.48) with chickens fed the control diet (100%FM) and progressively decreased with diet V (100%CWM) chickens recording the least (3.19). There was, however, no significant (p>0.05) difference between treatment means. Protein efficiency ratio followed similar trend with the feed conversion ratio. Diet I (100%FM) chickens had the highest value (2.09) followed by diet II (25%FM; 75%CWM) while those fed diet V (100%CWM) was the least (1.64).